03.22: Calculation model for moment ‐rotation relationship of bottom‐through‐diaphragm top‐ring connection between SST columns and HSS beams. (13th September 2017) - Cao, Shi; Shu, Ganping; Lin, Kunhong; Qin, Ying; Fan, Shenggang
ABSTRACT: Square steel tubular(SST) column and H‐shaped steel(HSS) beam systems have been widely used in engineering applications. The structural performance of this system largely depends on the behavior of the connections. This paper presents a new type of connections with bottom‐through‐diaphragm and top‐ring. Five specimens were tested under cyclic loadings to evaluate the seismic behavior and the moment‐rotation relationships. Finite element models were developed and compared with experimental testing to verify the accuracy of the model. The calculation equation of moment‐rotation curves were proposed according to the analytical data of finite element model. Furthermore, the moment‐rotation calculation model characterizing the general behavior of this new type connection were developed based on these parameters. The accuracy of the calculation model was examined by comparing with the results of finite element model. Finally, a reasonable moment‐rotation relationship was obtained using the parameters within this model.